Business Strategic Orientation and Banking Profitability: The Moderating Effect of Accounting Information Systems - Aldoury, Nashwan Ghazi Hameed; Kurter, Osman; Ahmed, Essia Ries (Universitas Muhammadiyah Surakarta, 2025)
The primary objective of this study is to examine the effect of business strategic orientation on organizational profitability. In addition, this study investigates the moderating role of the Accounting Information System (AIS); its dimensions of aggregation (AISA), integration (AISI), and timeliness (AIST), on the relationship between business strategic orientation and banking profitability. Chief Executive Officers (CEOs) and Chief Financial Officers (CFOs) were sample target subsets for this research. The chosen banks received a total of 152 questionnaires. A minimum of 113 respondents was considered a sufficient sample size based on the study's requirements. The Partial Least Squares (PLS) method was utilized to evaluate the survey data. Results indicate that cost leadership (BSCLS) has a positive but marginally significant effect on profitability, whereas innovative differentiation (BSID) significantly enhances banking profitability. Regarding the moderating role of AIS, aggregation (AISA) positively and significantly strengthened the cost leadership (BSCLS) profitability relationship but had a negative and significant moderating effect on the innovative differentiation (BSID) banking profitability link. AISI shows negative and insignificant moderation for cost leadership (BSCLS), and positive but insignificant moderation for innovative differentiation (BSID). AIST, negatively and significantly, moderates the cost leadership (BSCLS) profitability relationship, while it positively and significantly moderates the innovative differentiation (BSID) banking profitability relationship. These findings highlight that the effectiveness of strategic orientation on banking profitability is contingent on specific dimensions of the AIS.